Analisis Fundamental Saham Sebelum Dan Selama Pandemi Covid-19 Pada Perusahaan Sektor Industri Barang Konsumsi Yang Terdaftar Di Bursa Efek Indonesia Periode 2019 - 2020 - Syamsidar Syamsidar; Emmi Suryani Nasution; Nadia Ulfa (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
This study aims to test and analyze stock fundamental before and during the covid-19 pandemic. This research was conducted on consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the period 2019 – 2020. Observations in this study amounted to 50 issuers who have met the criteria. Data were analyzed using 4 financial ratios, namely Return on Assets (ROA), Return on Equity (ROE), Earning Per Share (EPS), and Price Earning Ratio (PER). The data analysis technique used is the two sample difference test in pairs. The result of this study indicate that there is no fundamental difference between before and during the covid-19 pandemic in consumer goods industrial sector companies listed on the Indonesia Stock Exchange for the 2019 – 2020 period.